Glacier sliding, seismicity and sediment entrainment. Issue 79 (September 2019) - Lipovsky, Bradley Paul; Meyer, Colin R.; Zoet, Lucas K.; McCarthy, Christine; Hansen, Dougal D.; Rempel, Alan W.; Gimbert, Florent
ABSTRACT: The evolution of glaciers and ice sheets depends on processes in the subglacial environment. Shear seismicity along the ice–bed interface provides a window into these processes. Such seismicity requires a rapid loss of strength that is typically ascribed to rate-weakening friction, i.e., decreasing friction with sliding or sliding rate. Many friction experiments have investigated glacial materials at the temperate conditions typical of fast flowing glacier beds. To our knowledge, however, these studies have all found rate-strengthening friction. Here, we investigate the possibility that rate-weakening rock-on-rock friction between sediments frozen to the bottom of the glacier and the underlying water-saturated sediments or bedrock may be responsible for subglacial shear seismicity along temperate glacier beds. We test this 'entrainment-seismicity hypothesis' using targeted laboratory experiments and simple models of glacier sliding, seismicity and sediment entrainment. These models suggest that sediment entrainment may be a necessary but not sufficient condition for the occurrence of basal shear seismicity. We propose that stagnation at the Whillans Ice Stream, West Antarctica may be caused by the growth of a frozen fringe of entrained sediment in the ice stream margins. Our results suggest that basal shear seismicity may indicate geomorphic activity.